2020
DOI: 10.1097/pec.0000000000002271
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardiac Point-of-Care Ultrasound in the Pediatric Emergency Department

Abstract: Objectives: We sought to describe the test characteristics of cardiac point-of-care ultrasound (POCUS) performed by pediatric emergency medicine (PEM) physicians after structured cardiac POCUS training. Methods: We evaluated the use of clinically indicated cardiac POCUS by PEM physicians in a single tertiary care pediatric emergency department after implementation of a focused cardiac POCUS training curriculum. The test characteristics of the sonologist interpretation were compared with expert POCUS review, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…As these patients are often toxic appearing and present similar to those with septic shock, broad spectrum antibiotics are recommended, with blood cultures obtained prior to antibiotic therapy when feasible. Given the potential for cardiogenic versus vasodilatory shock, point-of-care ultrasound should be performed prior to aggressive volume resuscitation [ 58 ]. Patients who are volume depleted based on either clinical examination or ultrasound should receive fluid resuscitation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As these patients are often toxic appearing and present similar to those with septic shock, broad spectrum antibiotics are recommended, with blood cultures obtained prior to antibiotic therapy when feasible. Given the potential for cardiogenic versus vasodilatory shock, point-of-care ultrasound should be performed prior to aggressive volume resuscitation [ 58 ]. Patients who are volume depleted based on either clinical examination or ultrasound should receive fluid resuscitation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that, after a short training, assessment of LV function by non-cardiologist physicians was strongly correlated to that made by a pediatric cardiologist [6,12,13]. Similarly, Miller et al [14] demonstrated that POCUS was highly sensitive and specific for LV systolic dysfunction in pediatric patients. In 2014, the American Society of Echocardiography (ASE) strongly recommended the use of cardiac POCUS in critically ill patients for specific scenarios, including evaluation of gross ventricular systolic function and cardiac arrest [15].…”
Section: Cardiac Myocardium Evaluationmentioning
confidence: 95%
“…Adult and pediatric studies have consistently demonstrated the accuracy by which non-cardiologists can identify pericardial effusions and cardiac tamponade by cardiac ultrasound [12,13,39,40]. Miller et al [14] demonstrated that cardiac POCUS was highly sensitive and specific for pericardial effusions in pediatric patients after a focused ultrasound training. In fact, the ASE strongly recommended the use of cardiac POCUS to assess for pericardial effusions in children [15].…”
Section: Pericardium Evaluationmentioning
confidence: 99%
“…FOCUS is both, sensitive and specific for identifying pericardial effusion and left ventricular systolic dysfunction when performed by non-experts with appropriate training ( 24 ). The latter, of course, is of major importance and needs to be updated regularly on a structured basis ( 25 , 26 ).…”
Section: Persistent Pulmonary Hypertension Of the Newbornmentioning
confidence: 99%